2010
DOI: 10.3851/imp1510
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adefovir dipivoxil monotherapy for up to 5 years in lamivudine-resistant chronic hepatitis B

Abstract: Adefovir dipivoxil salvage monotherapy for lamivudine-resistant CHB resulted in a modest cumulative virological response rate at 5 years, which was associated with progressive antiviral resistance. Consequently, adefovir monotherapy is not preferable as a first-line strategy for lamivudine resistance where combination lamivudine plus adefovir dipivoxil therapy is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 34 publications
2
44
2
Order By: Relevance
“…When genotypic resistance to ETV was suspected, it was analyzed with the method of restriction fragment mass polymorphism. 26 Endpoints and Definitions. The primary endpoint of this study was the serial analysis of qHBsAg and qHBeAg profiles in patients receiving ETV.…”
Section: Methodsmentioning
confidence: 99%
“…When genotypic resistance to ETV was suspected, it was analyzed with the method of restriction fragment mass polymorphism. 26 Endpoints and Definitions. The primary endpoint of this study was the serial analysis of qHBsAg and qHBeAg profiles in patients receiving ETV.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Likewise, high baseline DNA level (cut-off level of 10 5 -10 8 copies/mL) caused insufficient viral suppression, and even frequent emergence of resistance in ADV treatment for LAM-resistance CH-B patients. 8,10,19,20 Those phenomena may have resulted from a high replication rate and subsequent selection of a resistant strain. In this study, a chance to achieve IVR increased sharply by a log10 copies/mL decrement of HBV DNA level.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 However, not all LAM-resistant hepatitis B patients respond well to ADV treatment, some of them show partial or non-response and sometimes represent resistant mutations such as rtN236T and rtA181V/T. [7][8][9][10] Moreover, it is harder to manage CH-B showing combined resistance against LAM and ADV. The aim of this study was to identify factor(s) related to the efficacy of ADV treatment for LAM-resistant CH-B patients.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unavailability of TDF in many Asian countries, ADV has been used widely as a combination treatment regimen. However, due to the weak antiviral activity of ADV [28] and poor susceptibility for drug-resistant viral strains, suboptimal response is particularly common in patients who received LAM + ADV [29,30] . Evidence has shown that the persistence of suboptimal response during long-term antiviral treatment is associated with the emergence of multi-drug resistant viral strains, which could result in poorer clinical outcomes [31,32] .…”
Section: Discussionmentioning
confidence: 99%